Databook of nucleating agents - Wypych, Anna; Wypych, George (ChemTec Publishing, 2021)
"Databook of nucleating agents contains data on the most important products in use today. Two groups of data are included: data for chemical compounds used for the manufacture of nucleating agents (data included come from many available sources and contain extensive reference) and commercial products (data from a single supplier of material). The second edition contains revised data and includes commercial nucleating agents which are currently available."-- Provided by publisher.
Keywords: Polymers -- Additives.; Crystallization.; elektronické knihy; electronic books